New depth records and novel feeding observations of three elasmobranchs species in the Eastern Red Sea - Frappi, Sofia; Williams, Collin; Pilcher, Nicolas; Rodrigue, Mattie; Marshall, Paul; Pieribone, Vincent; Qurban, Mohammed; Duarte, Carlos M. (Frontiers in Marine Science, 2023)
Understanding the vertical distribution of elasmobranch species and associated ecological dynamics can be a crucial component of developing effective conservation strategies, particularly in light of their global population decline. Previous studies have primarily focused on horizontal extent and movement patterns of elasmobranchs, with limited knowledge about their vertical distribution. This knowledge gap stems from limited access to technological advancements and reliance on surface data from fisheries operations. Today, advancements in observing platforms such as electronic tracking, remotely operated vehicles and submersibles, and reductions in costs for drop cameras and BRUVs, allow for direct observation of animals at great depths, facilitating improved understanding of their ecological and trophic niches. This study reports new global depth records for three elasmobranch species observed in the Saudi Arabian Red Sea (Carcharhinus altimus, Rhinobatos punctifer, Iago omanensis), also presenting ethological evidence on Iago omanensis feeding behavior. Our findings have significant implications for conservation strategies and the development of targeted conservation measures. The provisioning of data on new depth ranges allows places like NEOM to better manage and protect deep sea habitats, due to the presence of species occurring at those depths.